Continuous assessment feedback giving approaches in the context of competence-based education training: a case study of the National Institute of Transport in Tanzania - Mkisi, Gilbert Eliah; Maro, Cyprian (Papers in Education and Development, 2024)
Feedback-giving is a critical component of continuous assessment within Competence-Based Education and Training (CBET). It enhances students’ skill development and deepen their understanding while also providing lecturers with insights into the effectiveness of the teaching-learning process. This study examined how continuous assessment feedback approaches were employed by lecturers at the National Institute of Transport to enhance students’ skill acquisition and comprehension of learning tasks. Guided by the interpretivist paradigm, the study utilised an exploratory case study design. Data were gathered through in-depth interviews, focus group discussions, and document reviews involving 19 lecturers and six students, selected using purposive and convenience sampling techniques. The findings indicate that most lecturers employed effective feedback methods, such as providing comments, returning completed tasks, and fostering lecturer-student engagement. The study concludes that these feedback-giving approaches play a significant role in promoting skill development and fostering a deeper understanding of learning tasks among students.